FEATURES OF ATTENTION DEVELOPMENT IN PRESCHOOL AGE CHILDREN - Rakhimova Feruza (Bright Mind Publishing, 2025)
This article discusses the theories and opinions of scientists about the emergence and development of attention in preschool children, that is, from 3 to 6 years old. First, we will consider what attention is and how important its role is in our lives.
Keywords: Preschool age, kindergarten age, attention, concentration, voluntary and involuntary attention, consciousness.